ISSUES OF INSTILLING NATIONAL VALUES IN THE MINDS OF YOUTH IN THE FORMATION OF A STRONG FAMILY (World Bulletin of Social Sciences, 2026)
This article examines the role of national values in the formation of a strong family institution and analyzes the mechanisms for instilling family responsibility, moral-ethical norms, and traditional upbringing methods in the consciousness of young people. In the context of globalization, the issues of preserving national identity, strengthening family stability, and guiding youth toward a healthy lifestyle are substantiated from theoretical and practical perspectives. The study emphasizes that sustainable family development requires the harmonization of traditional values with modern sociopsychological and economic approaches